Upper extremity pain and pitching mechanics in National Collegiate Athletic Association (NCAA) Division I softball - Oliver, G. D.; Gilmer, G. G.; Anz, A. W.; Friesen, K. B.; Brittain, A. R.; Goodlett, M. D.; Dugas, J. R.; Andrews, J. R. (International Journal of Sports Medicine, 2018)
The purpose of this study was to evaluate pitching mechanics between female softball pitchers with upper extremity pain and those without upper extremity pain. Specifically, the trunk, shoulder and elbow kinematics and shoulder kinetics during the change-up softball pitch were examined. Fifty-five collegiate softball pitchers participated, divided into those with upper extremity pain (20.0±1.3 yrs.; 174.4±6.9?cm; 82.9±12.4?kg; 11.1±2.6 yrs. of experience; n=23) and those who were pain-free (19.9±1.4 yrs.; 173.8±6.9?cm; 81.4±12.5?kg; 10.0±2.5 yrs. of experience; n=32). Pitching mechanics were obtained via the trakSTAR™ electromagnetic tracking system (Ascension Technologies, Inc., Burlington, VT, USA). Mann-Whitney U tests revealed significant differences in shoulder horizontal abduction at foot contact (p=0.014, U=153, Z=2.450) and trunk lateral flexion at ball release (p=0.012, U=150, Z=-2.515); and between shoulder distraction force at ball release (p=0.034, U=168, Z=-2.124). The pain group illustrated greater shoulder horizontal abduction at foot contact, less trunk lateral flexion towards the throwing side at ball release, and greater shoulder distraction at ball release than the pain-free group. The differences in trunk and shoulder kinematics, and shoulder kinetics between groups allows for insight into further studies examining injury pervasiveness in softball pitching.